The Usage of Lavender Aromatherapy in Managing Anxiety in Patients Who Are Undergoing Hemodialysis: A Systematic Literature Review - Dwi Bintari, Putri Agustina; Supriyatno, Heru - (Poltekkes Kemenkes Banjarmasin, 2024)
Background: Anxiety in hemodialysis patients can stem from the duration of undergoing hemodialysis treatment, limitations in daily activities, changes in social relationships, and concerns about sustaining life. Anxiety is a component of the quality of life for hemodialysis patients; thus, if it is not addressed promptly, it can lead to a decline in their quality of life, inhibiting and affecting the success of hemodialysis. Lavender aromatherapy serves as a relaxation therapy that can reduce anxiety levels in hemodialysis patients, characterized by its lack of side effects, safety for patients, non-invasive nature, and cost-effectiveness. Purpose: This writing aims to describe the use of lavender aromatherapy in managing anxiety among patients undergoing hemodialysis. Method: The method employed is a Systematic Literature Review through a qualitative approach. The literature search was conducted using the databases PubMed, Cochrane Library, DOAJ, Hindawi, Healey Library, Royal College of Nursing, UIC University Library, Neliti, and Google Scholar with formulated questions and Boolean Operators. Articles were filtered using various available filters, resulting in the selection of 7 relevant articles that served as references for the literature review. Keywords: Aromatherapy lavender; anxiety; hemodialysis